The Structure Features and Improving Effects of Polysaccharide from Astragalus membranaceus on Antibiotic-Associated Diarrhea - Shanshan Li; Yuli Qi; Duoduo Ren; Di Qu; Yinshi Sun (MDPI AG, 2019)
Astragalus membranaceus (Astragalus) is often used as a medical and food resource in China. The present study was designed to investigate the features and effects of polysaccharide from Astragalus membranaceus (WAP) on rats with antibiotic-associated diarrhea (AAD). WAP was mainly composed of glucose, galactose, arabinose and glacturonic acid, with glucan, arabinogalactan and RG-I regions, and it showed loosely irregular sheet conformation. WAP decreased the inflammatory cell infiltration of colon in AAD rats, increased propionate and butyrate production, improved metabolic levels, adjusted the diversity and composition of gut microbiota, increased the relative abundance of Pseudomonas, and decreased the relative abundance of Allobaculum and Coprococcus. In conclusion, WAP contained different types of polysaccharide regions and sheet three-dimensional conformation, while it ameliorated AAD by recovering the colon structure, adjusting the gut microbiota, and improving the SCFAs levels. The results can provide some data basis for natural products to alleviate the side effects related to antibiotics.